Diffuse Alveolar Hemorrhage Associated with Warfarin Therapy. (12th August 2015) - Kaya, Bülent; Yildiz, Ibrahim; Baha, Reshat Mehmet; Zeytun, Neslihan Ebru Eryaşar; Yetisgen, Azize
Abstract : Diffuse alveolar hemorrhage (DAH) is a life-threatening clinical pathologic syndrome caused by a variety of diseases. We report a case of DAH related to therapy of warfarin use. In this case report, we present the diffuse alveolar hemorrhage case as a rare and life-threatening complication of warfarin.